2016
DOI: 10.1373/clinchem.2015.245621
|View full text |Cite
|
Sign up to set email alerts
|

Multianalyte Conventional Reference Material (MacRM): A Useful Tool for Nationwide Standardization of Laboratory Measurements for Medical Care—A Model Study in Japan

Abstract: BACKGROUND:The Japanese Committee for Clinical Laboratory Standards (JCCLS) has developed a multianalyte conventional reference material (MacRM) for nationwide standardization of laboratory measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Further efforts should be made to produce commutable reference materials and to ensure that their use has a clear effect on the harmonization of patient results. It is reassuring that several national and international organizations, including the Joint Committee for Traceability in Laboratory Medicine, the WHO, and International Federation of Clinical Chemistry scientific division, have increased their focus on this issue lately (14,15 ). The large scatter that was seen around the regression line for several of the TSH assays indicates the possibility of different analytical specificity for these assays.…”
Section: Discussionmentioning
confidence: 99%
“…Further efforts should be made to produce commutable reference materials and to ensure that their use has a clear effect on the harmonization of patient results. It is reassuring that several national and international organizations, including the Joint Committee for Traceability in Laboratory Medicine, the WHO, and International Federation of Clinical Chemistry scientific division, have increased their focus on this issue lately (14,15 ). The large scatter that was seen around the regression line for several of the TSH assays indicates the possibility of different analytical specificity for these assays.…”
Section: Discussionmentioning
confidence: 99%
“…Although out of scope for the original C37 protocol, literature reports starting with the C37 protocol or very similar protocols have shown that supplementing a serum pool with a number of analytes has produced pools with elevated concentrations with acceptable commutability properties [11,12].…”
Section: Blood Collection and Processing Proceduresmentioning
confidence: 99%
“…Therefore, clinically significant variations may be overlooked if using the inter‐individual reference range alone. Also, observed variation, which may not be clinically significant, in the intra‐individual reference range, could be outside the inter‐individual reference range 1‐8 . Consequently, close monitoring of variations in the clinical laboratory results of an individual is difficult and can lead to unnecessary secondary examinations if the values obtained exceed the general reference range 1‐8 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, observed variation, which may not be clinically significant, in the intra‐individual reference range, could be outside the inter‐individual reference range 1‐8 . Consequently, close monitoring of variations in the clinical laboratory results of an individual is difficult and can lead to unnecessary secondary examinations if the values obtained exceed the general reference range 1‐8 . For example, serum enzymes, such as γ‐glutamyl transpeptidase and alkaline phosphatase, in addition to uric acid, total cholesterol, and albumin (ALB), have narrower intra‐individual variations than inter‐individual variations; thus, the reference range is consistent with inter‐individual variations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation